2010
DOI: 10.1124/jpet.110.167882
|View full text |Cite
|
Sign up to set email alerts
|

An Apolipoprotein E-Mimetic Stimulates Axonal Regeneration and Remyelination after Peripheral Nerve Injury

Abstract: Elevated apolipoprotein E (apoE) synthesis within crushed sciatic nerves advocates that apoE could benefit axonal repair and reconstruction of axonal and myelin membranes. We created an apoE-mimetic peptide, COG112 (acetyl-RQIKIWFQNRRMK-WKKCLRVRLASHLRKLRKRLL-amide), and found that postinjury treatment with COG112 significantly improved recovery of motor and sensory function following sciatic nerve crush in C57BL/6 mice. Morphometric analysis of injured sciatic nerves revealed that COG112 promoted axonal regrow… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
48
0
1

Year Published

2012
2012
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 69 publications
(53 citation statements)
references
References 40 publications
4
48
0
1
Order By: Relevance
“…Previous studies showed that the apoE-mimetic peptides, which were derived from the receptor-binding domain of apoE protein, (i.e., apoE133–149), could bind apoE receptors to simulate the bioactivities of the holo-protein (Li et al, 2006; Singh et al, 2008; Li et al, 2010). We first tested whether administration of apoE peptides could decrease the permeability of BSCB in apoE −/− mice following SCI.…”
Section: Resultsmentioning
confidence: 99%
“…Previous studies showed that the apoE-mimetic peptides, which were derived from the receptor-binding domain of apoE protein, (i.e., apoE133–149), could bind apoE receptors to simulate the bioactivities of the holo-protein (Li et al, 2006; Singh et al, 2008; Li et al, 2010). We first tested whether administration of apoE peptides could decrease the permeability of BSCB in apoE −/− mice following SCI.…”
Section: Resultsmentioning
confidence: 99%
“…3,5,8,9,[15][16][17][18][19][20][21][22][23][24]39,40 In the present study, we are the first to demonstrate a protective role of ApoE (133)(134)(135)(136)(137)(138)(139)(140)(141)(142)(143)(144)(145)(146)(147)(148)(149) in experimental acute kidney graft rejection. This effect was associated with a reduced influx of α/β TCR-expressing cells and CD8 pos cells as well as diminished expression of GrB and decreased levels of active caspase-3.…”
Section: Discussionmentioning
confidence: 60%
“…15 Furthermore, ApoE (133)(134)(135)(136)(137)(138)(139)(140)(141)(142)(143)(144)(145)(146)(147)(148)(149) can directly compete with the binding of ApoE to cell surface receptors. 15 Protective effects of exogenous ApoE and ApoE (133)(134)(135)(136)(137)(138)(139)(140)(141)(142)(143)(144)(145)(146)(147)(148)(149) were found in the context of several inflammatory disorders, [15][16][17][18][19][20][21][22][23][24] but their effect on the pathogenesis of acute organ rejection is still unknown.…”
mentioning
confidence: 99%
“…Lipid binding proteins, such as Apolipoproteins D and E (ApoD, ApoE), accumulate in the distal nerve portion after injury. ApoD is mainly expressed by endoneural fibroblasts, while ApoE is primarily produced by infiltrating macrophages (Li et al, 2010;Spreyer et al, 1990;Stoll and Muller, 1986).…”
Section: Macrophage-schwann Cell Interactionmentioning
confidence: 99%